The Theory and Practice of Corporate Risk Management: Evidence from the Field. Issue 4 (27th July 2018) - Giambona, Erasmo; Graham, John R.; Harvey, Campbell R.; Bodnar, Gordon M.
Abstract: We survey more than 1, 100 risk managers from around the world regarding their risk management policies. We find evidence consistent with some traditional theories of risk management, but not with all. We then study "why" or "why not" firms hedge and find that almost 90% of risk managers in nonfinancial firms hedge to increase expected cash flow. We also find that 70% to 80% of risk managers hedge to smooth earnings or to satisfy shareholders' expectations. Our analysis also suggests that regulatory changes implemented to increase market stability (e.g., Dodd‐Frank Act) could discourage corporate hedging. Finally, we provide evidence regarding hedging in six areas of risk: interest rate, foreign exchange, commodity, energy, credit, and geopolitical. We find that operational hedging is more common than financial hedging in all risk areas except foreign exchange.